Flexible Photonic Sensors: Flexible and Stretchable Photonic Sensors Based on Modulation of Light Transmission (Advanced Optical Materials 12/2019). Issue 12 (18th June 2019) - Peng, Wang; Wu, Hao
Abstract : Flexible and stretchable photonic sensors, which can be wrapped onto curved surfaces and deformed into different shapes, have inspired great research interest. In article number 1900329, Wang Peng and Hao Wu present recent progress in the development of flexible and stretchable photonic sensors, particularly photonic sensors based on the modulation of light transmission, from the aspects of materials synthesis and selection, structure design, fabrication methods, sensing characteristics and performances. The challenges and future research opportunities related to flexible and stretchable photonic sensors and their potential applications are also discussed.